Consumer Products Contributing to Fall Injuries in Children Aged <1 to 19 Years Treated in US Emergency Departments, 2010 to 2013: An Observational Study. (January 2019) - Ali, Bina; Lawrence, Bruce; Miller, Ted; Swedler, David; Allison, Jennifer
Consumer products are often associated with fall injuries, but there is limited research on nonfatal unintentional falls in children that examines both the child's age group and the involvement of consumer products and activities. We combined 2 data sources to investigate products and activities that contribute to fall injuries in children at different developmental ages (ie, <1, 1-2, 3-4, 5-9, 10-14, and 15-19 years). We analyzed data from the National Electronic Injury Surveillance System–All Injury Program for the years 2010 through 2013 and augmented it with product information from the National Electronic Injury Surveillance System. Between 2010 and 2013, children aged <1 to 19 years accounted for 11.1 million nonfatal unintentional fall-related emergency department visits. Fall injuries associated with home furnishings/fixtures were highest among children in age groups <1 year, 1 to 2 years, and 3 to 4 years. In the home furnishings/fixtures product group, beds were the leading contributor to falls. Fall injuries associated with sports/recreation were highest among children in age groups 5 to 9 years, 10 to 14 years, and 15 to 19 years. In this product group, monkey bars and basketball were the leading contributors to falls. Our findings indicate priority areas for falls injury prevention and intervention.